Changes in chemical properties and growth of corn in volcanic soils treated with peat, ground basalt pyroclastics, and calcium silicate - Boniao, R. D.; Shamshuddin, J.; Van Ranst, E.; S., Zauyah; Syed Omar, S. R. (2002)
Volcanic ash-derived soils have high pHo and very low cation exchange capacity attributed to their highly reactive colloidal constituents, the short-range-order minerals. Fertility is in doubt unless the effects of positive adsorption sites are masked and the increment of negative charge improved. Laboratory and glasshouse experiments were conducted to assess the masking effects of peat, ground basaltic pyroclastic and calcium silicate viz. effect on pH0 and CEC of volcanic soils of Camiguin Island, the Philippines, and to evaluate the growth of corn (Zea mays L.) grown on these soils after the treatments. In the laboratory experiment, Andic Haplumbrept (Soil 1) and Typic Dystrochrept (Soil 2) were incubated with 20% (air-dried) peat, ground basaltic pyroclastic and calcium silicate for nine months. In the glasshouse experiment, the treatments consisted of four rates of the above materials: 20, 10, 5, and 0% per unit weight soil. Corn was planted after nine months of incubation period. The results showed that incubation with peat reduced pH0, increased the CEC, and improved their ion retention. Addition of ground basaltic pyroclastic improved the charge properties but indicated that more incubation time is needed to get an optimum effect. Calcium silicate effect was uncertain due to a relatively high application rate. Corn response showed that nutrient uptake increased with the applied amendments. It also showed that relative plant heights and weights were linearly correlated with Mg concentration in the soil solution.